2019
DOI: 10.1002/jssc.201801066
|View full text |Cite
|
Sign up to set email alerts
|

Development of a highly sensitive gas chromatography–mass spectrometry method preceded by solid‐phase microextraction for the analysis of propofol in low‐volume cerebral microdialysate samples

Abstract: To date, the commonly used intravenous anesthetic propofol has been widely studied, and fundamental pharmacodynamic and pharmacokinetic characteristics of the drug are known. However, propofol has not yet been quantified in vivo in the target organ, the human brain. Here, cerebral microdialysis offers the unique opportunity to sample propofol in the living human organism. Therefore, a highly sensitive analytical method for propofol quantitation in small sample volumes of 30 μL, based on direct immersion solid‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For example, the LOD of propofol was determined to be 0.77 ng/mm 2 , which is equivalent to 3.7 μg mL –1 if the volume of standard solution spotted on the TLC plate (2 μL) is taken into account, while the therapeutic dose of propofol is 6–10 μg mL –1 for induction of anesthesia . While high uncertainty may result from the LOD being close to the application’s low end range requirements, fast and simple preconcentration methods, recently demonstrated for propofol, are readily available. , Also, the LOD for nicotine was determined as 0.20 ng/mm 2 (∼1.9 ng per sample spot), which shows better performance than the reported LOD of 2 μg for determination of nicotine in cigarettes by the SPME/GC-MS method . On the other hand, when using NP-TLC plates coupled with the LTP-MS system, some analytes cannot be quantified due to no or insufficient analytical response.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the LOD of propofol was determined to be 0.77 ng/mm 2 , which is equivalent to 3.7 μg mL –1 if the volume of standard solution spotted on the TLC plate (2 μL) is taken into account, while the therapeutic dose of propofol is 6–10 μg mL –1 for induction of anesthesia . While high uncertainty may result from the LOD being close to the application’s low end range requirements, fast and simple preconcentration methods, recently demonstrated for propofol, are readily available. , Also, the LOD for nicotine was determined as 0.20 ng/mm 2 (∼1.9 ng per sample spot), which shows better performance than the reported LOD of 2 μg for determination of nicotine in cigarettes by the SPME/GC-MS method . On the other hand, when using NP-TLC plates coupled with the LTP-MS system, some analytes cannot be quantified due to no or insufficient analytical response.…”
Section: Resultsmentioning
confidence: 99%
“…To date, many analytical techniques such as liquid chromatography-mass spectroscopy (LC-MS), 19,20 gas chromatography-mass spectrometry (GC-MS), 21,22 ion mobility spectrometry (IMS), 23–25 electrochemical 26 and electrochemiluminescence 27 have been successfully used for propofol analysis. Results revealed that the proposed method leads to higher extraction efficiency and sensitivities for the quantification of trace PF serum sample matrices, while it can also overcome some limitations of conventional HS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the importance of the determination of free levels for CNS drugs [4,17,25,27,28]. However, the analytical access to free levels is generally associated with considerable expenditure on equipment [29,30], especially in CSF, where the total concentrations of drugs are significantly lower compared to serum [25,31]. As protein levels in CSF are multiple orders of magnitude lower than in serum, protein binding is therefore usually neglected in CSF.…”
Section: Introductionmentioning
confidence: 99%